The EQ edge emotional intelligence and your success - Stein, Steven (Jossey-Bass, 2011)
REVISED AND UPDAT ED WITH NEW RESEARCH INTO EQ AND PERSONAL AND CAREER SUCCESS What is the formula for success at your job? As a spouse? A parent? A Little League baseball coach or behind the bench of a minor hockey team? What does it take to get ahead? To separate yourself from the competition? To lead a less stressful and happier existence? To be fulfilled in personal and professional pursuits? What is the most important dynamic of your makeup? Is it your A) intelligence quotient? or B) emotional quotient? If you picked "A", you are partly correct. Your intelligence quotient can be a predic.
Includes bibliographical references (pages 323-342) and index. - Print version record
Keywords: Emotional intelligence; Success -- Psychological aspects; Intelligence émotionnelle; Succès; Aspect psychologique; PSYCHOLOGY; Physiological Psychology; Success; Psychological aspects